The relationship between motivational type and athlete's perception of team environment - Bolding, Taylor (2018)
When it comes to team environment and motivation, there is no lack in research concerning different individual variables. Previous research is mainly concerned with the goup functioning as a singular entity, but rarely explores the individual aspect of group dynamics. Group cohesion studies comprise most of the research being done to establish a relationship between motivation and how this affects the perception of cohesion. More research is needed from an individual perspective when dealing with group environment because of the imperative role that individual characteristics play in pursuit of optimal team and group cohesion. Thus, the purpose of this study was to describe the relationship between an individual futsal team player’s motivational type, heir perception of team environment, and emotional awareness as compared to other team members with similar motivational types. The participants were six female futsal players in the highest level of the Finnish Futsal League. They all have played futsal for more than two years as teammates. Data regarding their motivational type was gathered through the Sport Motivation Scale-II (Peletier et al., 2013). The qualitative data regarding perception, emotional awareness and other aspects were gathered through a semi-structured interview. To analyze the data, Atlas.ti program was employed as to ascertain the different emergent and expected themes. Following this, the data was then rea-analyzed according to how they related to motivation, environment and emotional awareness. The results of the SMS-II revealed that four of the participants were strongly intrinsically motivated and two were split-mode motivated. Combining this information with what was gathered through the interviews, those who were more intrinsically motivated seemed to be more emotionally aware of their teammates and also played a vital role in how included they feel within the team environment. Along with this, there was also emergent themes regarding culture and failure avoidance. All subjects exhibited an aversion to making mistakes during trainings and games. In addition, half of them mention that the culture of Finland made it difficult to feel as though the team was a functioning unit. This exploration solidified the need for more research concerning environmental perception and motivational types within team sports.